NG2 cells in an animal model of congenital hydrocephalus - Jiménez-Lara, Antonio Jesús; Ojeda-Pérez, Betsaida; García-Bonilla, María; Ruz-Maldonado, Inmaculada; Mateos-Grondona, Jesús; Rodríguez-Pérez, Luis Manuel; Páez-González, Patricia (My University, 2017)
NG2 cells are considered oligodendrocyte precursor cells (OPC). In pathological conditions, NG2 cells contribute to generate oligodendrocytes and reactive astrocytes. This study has been designed to uncover the role of NG2 cells in congenital hydrocephalus using the hyh mouse model. Materials and methods Brain sections and whole mount preparations were obtained from embryos and postnatal hyh and control mice. NG2 positive (NG2+) cells were co-labelled with different IHC markers to deepest identification. Additionally, trying to understand reproducibility of our results in different neurodegenerative conditions, same NG2 identification approach was performed using ventricular walls explants from control mice after mechanical induction of astrocyte reaction. Results A higher number of NG2+ cells were found in the hyh mice compared to the control mice. In addition, NG2+ cells in the hyh mice showed a higher NG2 antigen content compared to the control mice. In the hyh mouse, colocalization results showed that most of NG2+ cells were identified as OPC cells and pericytes, but never as reactive astrocytes o microglial cells. However, in the same approach performed in neurodegenerative conditions, NG2+ cells were mostly identified as reactive astrocytes. Conclusions NG2 progenitors appear to be affected in hyh mutant mice giving rise to a different NG2+population which role in hydrocephalus is still unkown.
Comunicación oral. El resumen no se publica por deseo de los autores
Keywords: Hidrocefalia; Glía